Analysis of some variable performances of under 12 tennis players - Sannicandro, I.; Piccinno, A.; Cofano, G.; De Pascalis, S.; Rosa, A. R. (Medicina dello Sport, 2012)
Aim. The presence of a very reduced number of studies describing the tennis playing performance within a youth context conditions our awareness relating to the training methods of young tennis players. The study intends to describe the performative model of young tennis players (under 12) with particular reference to the total playing time, the effective playing time for each score, the recovery times between scores, game and set. The study equally intends to describe and quantify the main movement methods and number of changes of direction for each score realized by a young athlete during the game. Methods. The sample, consisting of 24 under 12 players of both Italian and foreign nationality (12 males, 44.7±3.7 kg, 153.7±6.1 cm, 12 females, 44.2±9.7 kg, height 159.7±8 cm), has been video filmed for subsequent detection in an appropriate table of any variable performances. Results. The study has shown gender differences in young tennis players in so far as the average time of the game`s duration is concerned (PConclusion. Youth tennis comes with very different values between the two genders and very far off from those of a top level tennis player; in view of these differences, specific programming would meanwhile be required for technical and athletic training sessions.